Citizen Diplomacy Strategies in Football Supporter Communities: A Case Study of Reconciliation Between PSS Sleman and PSIM Yogyakarta - Nurgiansah, T Heru; Danial, Endang; Rahmat; Mahpudz, Asep; Karim Suryadi; Nwokeocha, Ifeanyi Martins; Malihah, Elly (Jurnal Kewarganegaraan, 2025)
This article examines how rival football supporter communities in Yogyakarta, namely Slemania (PSS Sleman) and Brajamusti/Mataram Independent (PSIM Yogyakarta), interact. The urgency of this research is that citizen diplomacy is a critical new approach to de-escalating conflict while strengthening social bonds among supporters. The study identifies three key strategies within citizen diplomacy practiced by supporters: cross-group dialogue forums, collaborative social actions (such as blood donations and disaster relief), and digital campaigns aimed at reframing rivalry into an inclusive narrative of solidarity. Drawing on qualitative data from interviews and participant observation, the article analyzes practical implementation challenges, including intergenerational divides and institutional fragility. The findings suggest that while these initiatives remain uneven in reach, they have contributed to a significant reduction in intergroup violence and fostered renewed engagement with national identity among participants. This research offers empirical evidence that citizen-led diplomacy within football culture can serve as a transformative mechanism for social cohesion and civic integration in divided communities.